Peranan Kompetensi Profesional Guru Pendidikan Agama Kristen dalam Membentuk Karakter Peserta Didik - Naibaho, Septi Enjelika; Naibaho, Dorlan (Jurnal Pendidikan Non formal, 2023)
Nowadays, many problems that occur among Christian teenagers are caused by the lack of teaching Christian values and character to students. This can be caused by the progress of the times and also the increasingly rapid development of technology. However, on the other hand, the role of Christian Religious Education teachers can also help build good character for students at school. The task of Christian Religious Education teachers is to educate and guide students to become individuals who fear God. Character, if interpreted in general, is the nature, disposition or behavior that exists within a person and is a description of how he is. A student must have good character and fear God. The character of one person and another is certainly not the same, therefore character is said to be a description or characteristic of a person. In this case, it is important for Christian Religious Education teachers to understand what professional competencies are and apply them in the teaching and learning process. There are five competencies for Christian Religious Education Teachers that apply in Indonesia, including Pedagogical Competency, Personality Competency, Professional Competency, Social Competency and Spiritual Competency. As a teacher who is of course a role model for students, Christian Religious Education teachers must be professional in guiding and directing students because this will influence the formation of students' character and morals. The method used in writing this journal is the bibliographic method, meaning the method is carried out by examining various reference sources such as books, journals or scientific articles.